Kультурное производство: массовая культура и массовая литература - Норманская, А.В. (Культура народов Причерноморья, 2013)
В данном исследовании анализируется культурное производство в массовой культуре, в
т.ч. массовой литературе; рассматривается проблема разграничения литературы по гендерному
признаку, а также проблема манипуляторного воздействия продуктов массовой культуры на
потребителя.
Ключевые слова: массовая культура, массовая литература, культурное производство, «женская
проза», арт-рынок. В цьому дослідженні проаналізовано культурне виробництво в масовій культурі, в т.ч.
масовій літературі; розглянуто проблему розмежування літератури за гендерною ознакою, а також
проблему маніпуляторного впливу продуктів масової культури на споживача.
Ключові слова: масова культура, масова література, культурне виробництво, «жіноча проза», арт-
ринок. This study article the cultural production in mass culture, including popular literature, the problem
of separation of the literature on gender and the problem of manipulator effects of the products of popular
culture on the consumer.
Relevance of the article . Popular culture has a distinct consumer nature and is designed for the most common
human feelings, instincts and emotions. This results in the leveling of cultural values and ideals, including those
in the literature. The production is the cultural the basis of popular culture. This assertion follows from the term
"cultural production" First, popular culture is closely linked to large runs, and second, mass culture is based on
stereotypes and certain matrices work.
The aim of the study is to analyze the cultural production in popular culture as a whole, as well as an example of
one of the most popular genres of popular literature - melodrama or "women's prose."
Sales promotion-text on the market of mass literature sometimes determined by the membership's the female or
male sex. Issue of gender criteria popular literature remains open and is, in our view, an artificial, advertising
and superficial, gender has no effect on the consumer perception of the text as issues relevant work regardless of
sex author, and from the author's position.
Main tasks:
 analyze the cultural production as a basis for the development of mass culture;
 determine the mechanisms of cultural production to ensure the success of the popular literature;
 show the market a product of the contemporary art market as an example of "women's prose."
Keywords: mass culture, mass literature, cultural production, "women's fiction", the art market.